Simulated Predator Extinctions: Predator Identity Affects Survival and Recruitment of Oysters - O'Connor, N.E; Grabowski, J.H; Ladwig, L.M; Bruno, J.F (Ecology (Durham), 2008)
The rate of species loss is increasing at a global scale, and human-induced extinctions are biased toward predator species. We examined the effects of predator extinctions on a foundation species, the eastern oyster (Crassostrea virginica). We performed a factorial experiment manipulating the presence and abundance of three of the most common predatory crabs, the blue crab (Callinectes sapidus), stone crab (Menippe mercenaria), and mud crab (Panopeus herbstii) in estuaries in the eastern United States. We tested the effects of species richness and identity of predators on juvenile oyster survival, oyster recruitment, and organic matter content of sediment. We also manipulated the density of each of the predators and controlled for the loss of biomass of species by maintaining a constant mass of predators in one set of treatments and simultaneously using an additive design. This design allowed us to test the density dependence of our results and test for functional compensation by other species. The identity of predator species, but not richness, affected oyster populations. The loss of blue crabs, alone or in combination with either of the other species, affected the survival rate of juvenile oysters. Blue crabs and stone crabs both affected oyster recruitment and sediment organic matter negatively. Mud crabs at higher than ambient densities, however, could fulfill some of the functions of blue and stone crabs, suggesting a level of ecological redundancy. Importantly, the strong effects of blue crabs in all processes measured no longer occurred when individuals were present at higher-than-ambient densities. Their role as dominant predator is, therefore, dependent on their density within the system and the density of other species within their guild (e.g., mud crabs). Our findings support the hypothesis that the effects of species loss at higher trophic levels are determined by predator identity and are subject to complex intraguild interactions that are largely density dependent. Understanding the role of biodiversity in ecosystem functioning or addressing practical concerns, such as loss of predators owing to overharvesting, remains complicated because accurate predictions require detailed knowledge of the system and should be drawn from sound experimental evidence, not based on observations or generalized models.